The Collateral Impacts of Pandemic - Ceva Wicaksono Pitoyo (Acta Medica Indonesiana, 2020)
A pandemic that covers the whole world occurs relatively in every 100 years. Thus, it can be said that no expert has ever experienced directly dealing with a global pandemic. In the absence of people who are truly experts who know the problems and impacts of a global pandemic, various studies need to be carried out extensively between fields and across regions in the world. Likewise, the results of the study need to be recorded permanently so that it can still be useful over a long period of time, preferably for more than a hundred years.